2021
DOI: 10.4269/ajtmh.21-0386
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Dengue Infection Using IgG Capture ELISA in India, 2017–2018

Abstract: We conducted a nationally representative population-based survey in 60 districts from 15 Indian states covering all five geographic regions during 2017–2018 to estimate the age specific seroprevalence of dengue. Of the 12,300 sera collected, 4,955 were positive for IgG antibodies against dengue virus using IgG Indirect ELISA indicating past dengue infection. We tested 4,948 sera (seven had inadequate volume) positive for IgG antibodies on indirect ELISA using anti-dengue IgG capture ELISA to estimate the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…DENV seroprevalence in Southern Malaysia was reported to be 86.6% based on Panbio IgG indirect ELISA with a positive rate of 11.2% based on Panbio IgG-capture ELISA [ 23 ]. Similarly, DENV seroprevalence was reported to be 85–90% and 81.4% based on Panbio indirect IgG ELISA in Columbia and India, respectively, with positive rates of 16% and 8.1% based on Panbio IgG-capture ELISA [ 24 26 ]. Another study reported DENV seroprevalence of 8.9% based on Panbio indirect IgG ELISA with a 1.4% positive rate based on Panbio IgG-capture ELISA in Madeira Island [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DENV seroprevalence in Southern Malaysia was reported to be 86.6% based on Panbio IgG indirect ELISA with a positive rate of 11.2% based on Panbio IgG-capture ELISA [ 23 ]. Similarly, DENV seroprevalence was reported to be 85–90% and 81.4% based on Panbio indirect IgG ELISA in Columbia and India, respectively, with positive rates of 16% and 8.1% based on Panbio IgG-capture ELISA [ 24 26 ]. Another study reported DENV seroprevalence of 8.9% based on Panbio indirect IgG ELISA with a 1.4% positive rate based on Panbio IgG-capture ELISA in Madeira Island [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…of samples Source of study (No.) Confirmation Country and year pDENV 42 seroprevalence study [ 20 ] Neutralization test b Taiwan, 2015-16 [ 33 ] Neutralization test b Brazil, 2016-17 [ 37 ] DENV study [ 7 ] RT-PCR Taiwan, 2001-9 [ 35 ] DENV study [ 11 ] RT-PCR Hawaii, 2015 [ 35 ] sDENV 88 seroprevalence study [ 39 ] Neutralization test b Taiwan, 2015-16 [ 33 ] ZIKV study [ 21 ] Neutralization test b Brazil, 2016-17 [ 37 ] DENV study [ 26 ] RT-PCR Taiwan, 2001-9 [ 35 ] DENV study [ 2 ] RT-PCR Hawaii, 2015 [ 35 ] DENV-naïve 49 seroprevalence study (49) Neutralization test b or multiple ELISAs …”
Section: Methodsmentioning
confidence: 99%
“…In patients with either dengue NS1 and/or IgM, positivity with high IgG levels indicates secondary dengue and can be detected as early as 3 days post onset of illness till 15 days. A positive result (>22 Panbio™ units) in Panbio™ Dengue IgG Capture ELISA was considered as active secondary infection ( Santhosh Kumar et al., 2021 ). The viral load in the daily collected serum samples was estimated using real-time RT-PCR targeting the untranslated region (UTR) of DENV, as described previously ( Gurukumar et al., 2009 ).…”
mentioning
confidence: 99%